A novel phosphodiesterase-5 Inhibitor: Yonkenafil modulates neurogenesis, gliosis to improve cognitive function and ameliorates amyloid burden in an APP/PS1 transgenic mice model. (September 2015) - Zhu, Lei; Yang, Jing-yu; Xue, Xue; Dong, Ying-xu; Liu, Yang; Miao, Feng-rong; Wang, Yong-feng; Xue, Hong; Wu, Chun-fu
Highlights: Yonkenafil improves cognitive deficits in AD mice. Yonkenafil reduces the β-amyloid burden. Yonkenafil inhibits the activation of microglia and astrocytes. Yonkenafil protects hippocampal neurogenesis in AD. Abstract: In Alzheimer's disease (AD), activated microglia invade and surround β-amyloid plaques, possibly contributing to the aggregation of amyloid β (Aβ), which affect the survival of neurons and lead to memory loss. Phosphodiesterase-5 (PDE-5) inhibitors have recently been shown a potential therapeutic effect on AD. In this study, the effects of yonkenafil (yonk), a novel PDE-5 inhibitor, on cognitive behaviors as well as the pathological features in transgenic AD mice were investigated. Seven-month-old APP/PS1 transgenic mice were treated with yonk (2, 6, or 18 mg/kg, intraperitoneal injection (i.p.)) or sildenafil (sild) (6 mg/kg, i.p.) daily for 3 months and then behavioral tests were performed. The results demonstrated that yonk improved nesting-building ability, ameliorated working memory deficits in the Y-maze tasks, and significantly improved learning and memory function in the Morris water maze (MWM) tasks. In addition, yonk reduced the area of Aβ plaques, and inhibited over-activation of microglia and astrocytes. Furthermore, yonk increased neurogenesis in the dentate granule brain region of APP/PS1 mice, indicated by increased BrdU + /NeuN + and BrdU + /DCX + cells compared to vehicle-treated transgenic mice. These results suggest that yonk could rescue cognitive deficits by ameliorated amyloid burden through regulating APP processing, inhibited the over-activation of microglia and astrocytes as well as restored neurogenesis.